The Evangelical theology of the Orthodox church - Nassif, Bradley (St Vladimir's Seminary Press, 2021)
The Evangelical Theology of the Orthodox Church: In Worship, Spirituality, and Doctrine -- Orthodoxy and Evangelicalism in Dialogue.